Use of sorghum with different tannin contents in diets for growing and fattening pigs (Semiárida, 2020)
Two feeding trials were carried out with crossed pigs using grain sorghums as the only energetic source with different tanin levels according to Follin Denis analysis. Grain sorghums were supplied with proteins, minerals and vitamins. Thirty six barrows were used in the first trial, in two treatments with three repetitions each one with pigs weighing from 39 K to 105 K average live weight. Two sorghums were used, one with 0,37% tanin (T1) and other with 1,8% (T2). Differences were significative in daily gain (0,924 vs 0,783, P≤0,01) daily intake (3,420 vs 3,860, P 0,05), and feed/gain (3,70 vs 4,93, P< 0.01) unfavorable for T2. Four milling mixing sorghums with different levels of tannin 2%. 1,5%, 1% and 0,5% were used on the second trial. All diets were made isoprotein with soybean meals and a commercial supply of protein mineral vitamins with 35% of BP. No significative differences were found at level P
Keywords: pig